The drive-through COVID-19 vaccination in Yogyakarta - Chandra, Lukman Ade; Nirwati, Hera; Puspitasari, Ika; Dibtyanusa, Ajib; Sutono, Sutono; Achmad, Bayu Fandi; Kumara, Intan Fatah; Siswishanto, Rukmono (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Introduction: COVID-19 vaccination is the government's priority to control viral transmission. Drive-through system provides quick means of product or service delivery; however, it has not been extensively adopted as a vaccination method. This study aims to describe the implementation of the drive-through COVID-19 vaccination conducted by the Faculty of Medicine, Public Health, and Nursing at Universitas Gadjah Mada in collaboration with several national and regional, governmental and non-governmental institutions. Methods: The drive-through vaccination involved online registration, data collecting, reporting, on-site dose preparation, injection, and post-vaccination monitoring while participants remained in their vehicles. The events were scheduled between July and September 2021 in either FK-KMK UGM Campus or Grha Sabha Pramana, UGM. These venues are on the inner property side of UGM, therefore is no disruption of public traffic. Participants who are eligible and receive an invitation may attend the immunization venue according to the schedule. Results: In ten vaccination events, 20,870 doses of the COVID-19 vaccine were administered. Most participants were young people, with slightly more women than men. The drive-through vaccination went relatively well and offered many benefits such as improving vaccine coverage, time efficiency, social distancing, and herd immunity. Yet, issues like mild Adverse events following immunization and an accumulation of vehicles occurred. Therefore, careful planning and risk anticipation are necessary. Conclusion: The drive-through vaccination generally provides rapid and safe vaccine delivery to large communities. This method could be an alternative to delivering mass vaccinations requiring rapid and extensive coverage.